Delayed Visual Maturation – A Clinical Case - Corbeil, Marie-Eve (Canadian Journal of Optometry, 2009)
A first eye examination is performed on a two and a half month old patient who presents with no visual response to fixation or to pursuing a target or a light despite an unremarkable ocular health assessment. This temporary eye condition is known as Delayed Visual Maturation (DVM). Conclusion: A subsequent eye examination was performed at age five and a half months only to reveal that the child’s visual behaviour was now considered to be appropriate for his age. The diagnosis of DVM remains a diagnosis of exclusion and requires a comprehensive eye examination, electrodiagnostic testing and imaging techniques which may eventually include MRI.